Assessment of phytotoxic potential of oil palm leaflet, rachis and frond extracts and powders on goosegrass (Eleusine indica (L.) Gaertn.) germination, emergence and seedling growth - Chuah, T.S.; Lim, W.K. (Penerbit Universiti Kebangsaan Malaysia, 2015)
In order to achieve higher yields and protect crops from competition with weeds, various herbicides are widely employed in plantations and farms. However, the excessive use of herbicides has caused adverse impact to agricultural areas and water sources through the process of leaching and water infiltration besides causing herbicide resistance in weeds like goosegrass (Eleusine indica (L.) Gaertn.). This study aimed to determine the phytotoxic potential of oil palm residue extracts and residues on goosegrass under laboratory and glasshouse conditions. Crude extracts of oil palm residues, viz; leaflet, rachis or frond was applied onto Petri dishes containing goosegrass seeds. Leaflet, rachis or frond powder was manually applied as mulching on the soil surface sown with goosegrass seeds. Rachis powder was the most effective treatment where it reduced emergence and growth of goosegrass seedlings by approximately 20 and 50% at 4 t ha-1, respectively, while the rachis extract provided complete inhibition of goosegrass germination at a concentration of as low as 1.0% (w/v). These results suggest that oil palm rachis powder has the potential to be an alternative to commercial herbicides for goosegrass control.